AN ANALYSIS OF SUPPLY - DEMAND CHARACTERISTICS, TECHNOLOGICAL TRENDS, AND CONTINUING EDUCATION NEEDS IN DERMATOLOGY SERVICES IN THE MEKONG DELTA (Vietnam Journal of Community Medicine, 2026)
In recent years, the rapid increase in the prevalence of dermatological diseases and the growing demand for aesthetic procedures have created a massive market demand, driving the introduction of a wide range of new technologies and products. However, the development of high-quality and sustainable dermatology services in the Mekong Delta region—a tropical area with distinct economic and environmental characteristics—is currently facing several challenges.Objective: To assess the characteristics of human resources (supply) and market demand (demand) for dermatological services; and to analyze the current status and future needs regarding technology application and continuing education in the field. Methods: This study employed a descriptive cross-sectional design involving 128 physicians directly engaged in dermatological and cosmetic dermatology activities. Results: On the Demand side, the market is undergoing a dual transition: maintaining a high prevalence of common pathologies (acne vulgaris at 57.8% and dermatitis at 50.0%) while strongly shifting towards specialized aesthetic needs [keratosis (p = 0.032), striae distensae (p = 0.022), and telangiectasia (p = 0.027)]. On the Supply side, the dermatology sector is responding by rejuvenating its workforce (57.8% of physicians having 1–5 years of experience) and consolidating its core strength at the initial postgraduate level (Physicians/Specialist Level I/Masters holding 68%). The current status of technology application shows that Laser remains the essential and dominant tool, while demand for aesthetic injectables (Filler 29.7%, Botox 25.8%) and non-invasive lifting technologies (HIFU, MFU 24.2%) is increasing. Conclusion: Dermatological market demand is increasing and strongly shifting from the treatment of common pathologies to specialized aesthetic services, while the specialized workforce is being rejuvenated, demonstrating good adaptability to the trend of prioritizing rapid intervention, minimal downtime, and comprehensive rejuvenation solutions.
Keywords: dermatological diseases, acne vulgaris, dermatitis, aesthetic injectables, non-invasive lifting, laser